Development and Characterization of Herbal Extract-Loaded Nanoemulgels for Periorbital Hyperpigmentation and Edema: Antioxidant, Anti-inflammatory, and Anti-tyrosinase Activities - Ebru Altuntaş; Vildan Manav; Merve Yılmaz; Ayşe Esra Karadağ (Journal of Pharmaceutical Innovation, 2026)
Purpose Periorbital dark circles and edema are frequent cosmetic concerns that contribute to an older and fatigued appearance, thereby diminishing self-esteem and overall quality of life. Conventional topical regimens are often limited by the low stability, poor aqueous solubility, and insufficient epidermal penetration of many active compounds. To address these problems, we developed and characterized nanoemulgel (NEG) formulations utilizing standardized extracts of Glycyrrhiza glabra (G. glabra ) and Aesculus hippocastanum (A. hippocastanum ). These formulations were designed as multifunctional topical platforms with potential relevance to both pigmentation-related and edema-associated periorbital concerns. Methods Oil-in-water nanoemulsions (NEs) were prepared by ultrasonication using Quillaja saponin alone or combined with Kolliphor ® P188 and subsequently gelled with xanthan gum. Physicochemical properties (droplet size, polydispersity index (PDI), zeta potential, pH, viscosity, and conductivity) and stability were evaluated. Antioxidant (DPPH, ABTS), anti-inflammatory (lipoxygenase inhibition), and anti-tyrosinase activities were assessed. Results Among the generated NEGs, two formulations exhibited distinct physicochemical profiles. The saponin-based formulation F3P2 exhibited a droplet size of 142.70 ± 1.90 nm, a PDI of 0.184 ± 0.01, and a markedly negative zeta potential of − 59.0 ± 3.3 mV, signifying strong electrostatic stabilization. In contrast, the hybrid formulation F6P2, which integrates saponin with Kolliphor ® P188, demonstrated a reduced droplet size of 136.48 ± 1.8 nm, a decreased PDI of 0.102 ± 0.00, and a zeta potential of − 46.8 ± 2.5 mV, indicating improved size uniformity. Both formulations exhibited stability at the nanoscale (< 200 nm) throughout accelerated and three-month stability evaluations. F6P2 showed the most favorable overall biological profile among the tested formulations, demonstrating pronounced antioxidant properties (DPPH IC₅₀ = 22.65 µg/mL; ABTS IC₅₀ = 10.42 µg/mL), along with 80.11 ± 0.04% inhibition of lipoxygenase and 76.9 ± 0.03% inhibition of tyrosinase at a dosage of 20 µg/mL. Conclusion The developed NEGs loaded with G. glabra and A. hippocastanum demonstrated robust nanoscale stability together with notable antioxidant, anti-inflammatory, and anti-tyrosinase activities. The findings indicate that both biosurfactant-based and hybrid surfactant systems can be strategically tailored to balance colloidal stability and biological performance. Their potential as innovative dermocosmetic platforms for periorbital concerns is supported by their multifunctional relevance to pigmentation- and edema-associated pathways, warranting further in vivo evaluation.